Perspectives on the Role of Photodynamic Therapy in the Treatment of Pancreatic Cancer - Wei Li; Qingyong Ma; Erxi Wu (International Journal of Photoenergy)
Photodynamic therapy (PDT) is a noninvasive procedure involving a photosensitizing agent that is activated by light to produce reactive oxygen species (ROS) that selectively destroy tumor cells. In recent years, PDT has been used in the treatment of pancreatic cancer (PC). The antitumor effects of PDT include three main mechanisms: direct tumor cell death (necrosis, apoptosis, and autophagy), vascular destruction, and immune system activation. The present paper systematically summarizes the effects of PDT in the treatment of PC from the experimental studies to the clinical studies and discusses the mechanisms of PDT-induced PC destruction.